Legalitas Fintech Peer To Peer Lending Pinjaman Online dalam Aspek Hukum Konvensional - Seri Mughni Sulubara; Amrizal Amrizal (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Online loans are financial assistance from financial institutions that is done online, which is one proof of the advancement of financial technology (fintech). Online lending or peer to peer lending as a form of financial technology (fintech) is a technological advancement that offers loans with easier and more flexible terms and conditions. The theory used in this research is the theory of legal legality. The theory of legal legality is very relevant to the research made here, because there needs to be legal legality of peer to peer lending in online loans in conventional law considering that the payment system in this illegal online lending and borrowing service has troubled many people, such as intimidative billing, dissemination of personal data, fraud, and sexual harassment through electronic media. The research method used is qualitative descriptive research. The data collection technique or instrument used is library research by studying various books as literature, official documents, laws and regulations, results of previous research, and other literature sources related to the problems studied. The legality of fintech peer to peer lending online loans in the aspect of conventional law is found in the Financial Services Authority Regulation Number 77/POJK.01/2016 concerning Information Technology-Based Money Lending and Borrowing Services, Law Number: 8 of 1999 concerning Protection of Consumer Protection and Law Number: 11 of 2008 concerning Information and Electronic Transactions and other applicable regulations.